Digital Transformation in Indonesian Maritime Education: A Qualitative Study on Technology-Enhanced Learning - Elis Kardiono, Devega (Meteor STIP Marunda, 2025)
This research critically examines the integration of digital technologies in maritime education at Sekolah Tinggi Ilmu Pelayaran (STIP) Indonesia and its impact on graduate competency development. Through a qualitative approach involving in-depth interviews with graduates, educators, and industry stakeholders, along with document analysis, the study reveals a significant "pedgagogy-technology gap." While STIP Indonesia has successfully established robust digital infrastructure, including advanced simulators, findings indicate that technological access alone is insufficient for developing comprehensive maritime competencies. The research identifies three critical barriers: constrained access to digital resources, misalignment between technology use and pedagogical approaches, and varying levels of instructor digital proficiency. These factors collectively limit the development of higher-order digital fluency and analytical mindset needed in modern maritime operations. The study contributes to maritime education literature by demonstrating that effective digital transformation requires parallel investments in curriculum redesign, faculty development, and pedagogical innovation alongside technological infrastructure. Practical implications suggest strategic rebalancing of resources and enhanced industry-academia collaboration to bridge the competency gap and strengthen Indonesia's maritime workforce readiness in the era of Industry 4.0.